2017
DOI: 10.1080/13880209.2017.1279673
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of chemical constituents from the aerial parts of Hedyotis pilulifera

Abstract: Context:Hedyotis pilulifera (Pit.) T.N. Ninh (Rubiaceae) has been used in Vietnamese ethnomedicine; the methanol extract exhibited antibacterial activity in our preliminary screening.Objectives: In this study, compounds from H. pilulifera were isolated and their antibacterial activity in vitro was evaluated.Materials and methods: The aerial parts of H. pilulifera (1.4 kg) were extracted with MeOH, suspended in water and ethyl acetate extract was chromatographed on a silica gel column. The structures of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…[22][23] Previous studies on octadecane derivative showed the moderate inhibitory effect against bacterial strains. 24 Another study of oil comprising of hexahydrofarnesyl acetone constituent has reported for its antimicrobial effect. 25 The fatty acid (Methyl ester) reported for moderate antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23] Previous studies on octadecane derivative showed the moderate inhibitory effect against bacterial strains. 24 Another study of oil comprising of hexahydrofarnesyl acetone constituent has reported for its antimicrobial effect. 25 The fatty acid (Methyl ester) reported for moderate antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest MIC against S. aureus were observed for the mixture of lipid classes from the aerial parts of Hedyotis pilulifera (1.25 µg/mL) [83], the artemceramide-B from the roots of A. incisa (0.0313 mg/mL) [73], the linoleate oxylipins isolated from Alternanthera brasiliana (50 µg/mL) [65], and the FAME extracted from the shoots of Salicornia brachiata (60 µg/mL, the same MIC also verified for a MRSA strain) [61]. In the case of artemceramide-B, its high inhibitory potential against S. aureus was assigned to this polar lipid bearing four hydroxyl groups and an amide linkage between two long aliphatic chains [73].…”
Section: Susceptibility Testing Inhibitory and Microbicidal Activitmentioning
confidence: 95%
“…To identify and/or quantify mixtures of compounds, simpler techniques can be applied as biochemical assays using colorimetric tests, as for instance, for sterols' and steryl glycosides' identification and quantification [68,69,72]. The data obtained for compounds' identification in these studies on antimicrobial plant lipids are normally compared with data reported in the literature, especially for spectroscopic data [72,83].…”
Section: Extraction and Isolation Of Plant Lipidsmentioning
confidence: 99%
“…Since the 1940s, the analysis of the sources of new and approved drugs indicated that about 47% of all approved antitumor drugs are either natural products or directly derived therefrom [2]. We have previously reported [3][4] phytochemicals and antibacterial activity of Hedyotis pilulifera (Pit.) T.N.Ninh collected in Vietnam.…”
mentioning
confidence: 99%
“…Twenty-one compounds were isolated from the aerial parts of H. pilulifera and identified as follows: oleanolic acid (1), betulinic acid (2), pomolic acid 3β-acetate (3), rotungenic acid (4), rotundic acid (5), daucosterol (6), octadeca-9Z,12Z-dienoic acid (7), (7S*,8R*,7R*,8S*)-icariol A2-9-O-β-xylopyranoside (8), 10-Oacetylborreriagenin (9), asperuloside (10), paederoside (11), asperulosidic acid (12), daphylloside (13), paederosidic acid methyl ester (14), adenosine (15) (21). The isolation processes and structural elucidations of these compounds were reported in our previous publications [3][4][5]11].…”
mentioning
confidence: 99%